Clinical Cadavers as a Simulation Resource for Procedural Learning. Issue 3 (6th June 2018) - Kovacs, George; Levitan, Richard; Sandeski, Rob
Abstract: "See one, do one, teach one" remains an unofficial, unsanctioned framework for procedural skill learning in medicine. Appropriately, medical educators have sought alternative simulation venues for students to safely learn their craft. With the end goal of ensuring competence, educational programming will require the use of valid simulation with appropriate fidelity. While cadavers have been used for teaching anatomy for hundreds of years, more recently they are being repurposed as a "high‐fidelity" procedural skill learning simulation resource. Newly deceased, previously frozen, and soft‐preserved cadavers, such as those used in Baltimore and Halifax, produce clinical cadavers with high physical and functional fidelity that can serve as simulators for performing many high‐acuity procedures for which there is otherwise limited clinical or simulation opportunities to practice. While access and cost may limit the use of cadavers for simulation, there are opportunities for sharing resources to provide an innovative procedural learning experience using the oldest of medical simulation assets, the human body.